(untitled) (Global Journal of Management and Business Research, 2016)
A plethora of studies have been done on the effect of trade and financial integration on growth-volatility relationship. One of the key findings has been that, trade integration and financial integration weaken growth-volatility relationship. Trade integration is empirically found to positively affect growth significantly but results were less robust for financial integration. This paper finds that, by controlling for some key variables in addition to the variables used in the literature, as well as using alternate classifications and extending the data slightly the coefficient of financial integration is also positive and robust and hence weakens growth-volatility relationship. However, results for trade integration become insignificant after controlling for these crucial variables.